Correlation of Body Mass Index and Estimated Glomerular Filtration Rate in Patients with Rheumatic Heart Disease at Tertiary Care Hospital - Shreewastav,, Rupesh Kumar; Nepal, Rajesh; Dhungana, Sahadeb Prasad; Singh, Arambam Giridhari (Birat Journal of Health Sciences, 2020)
Introduction: Rheumatic heart disease (RHD), the leading causes of acquired heart disease worldwide, is a major health problem in developing countries. Rheumatic Heart Disease (RHD), affecting the heart valve system, leading to congestive heart failure and arrhythmias. The effects of body mass index (BMI) on kidney function have been reported and become a subject of increased concern. BMI is strongly associated with decreased eGFR in healthy persons. But the association between BMI and eGFR is not well characterized in chronic disease like RHD. Objective: The aim of this study was to investigate the association between body mass index (BMI) and estimated glomerular filtration rate (eGFR) among RHD patients as studies have evaluated the significance BMI as a risk factor for the development of kidney diseases. Methodology: It was an analytical cross-sectional study, which was conducted in a tertiary care hospital. A questionnaire was used to record the demographic characteristics of the patients. Height in meter and weight in kg of the study patients were recorded to calculate body mass index. Serum creatinine level of the patients was estimated in the clinical laboratory and estimated glomerular filtration rate was calculated by cockroft-Gault formula. The data was analyzed into SPSS 20.0 V Results: The total number of rheumatic heart disease patients enrolled in this study was 120. The Mean ± Standard deviation values of body mass index, serum creatinine and estimated glomerular filtration rate of all the patients were 21.39 ± 3.91 kg/m2, 0.93 ± 0.41 mg/dl and 69.53±19.4 ml/min respectively. Increased body mass index was associated with reduced estimated glomerular filtration rate (r = -0.04) of the patients. Similarly, body mass index showed negative correlation with that of serum creatinine (r = -0.03) and also with that of age (r = -0.05) of the patients. Age (r = -0.043) and serum creatinine (r = -0.056) of the patients were negatively correlated with estimated glomerular filtration rate. Conclusion: The study reveals that in rheumatic heart disease, body mass index is negatively but non-significantly associated with estimated glomerular filtration rate.